Risk factors for injuries in football - Arnason, A.; Sigurdsson, S. B.; Gudmusson, A.; Holme, I.; Engebretsen, L.; Bahr, R. (The American Journal of Sports Medicine, 2004)
BACKGROUND: The injury risk in football is high, but little is known about causes of injury. PURPOSE: To identify risk factors for football injuries using a multivariate model. STUDY DESIGN: Prospective cohort study. METHODS: Participants were 306 male football players from the two highest divisions in Iceland. Before the 1999 football season started, the following factors were examined: height, weight, body composition, flexibility, leg extension power, jump height, peak O(2) uptake, joint stability, and history of previous injury. Injuries and player exposure were recorded throughout the competitive season. RESULTS: Older players were at higher risk of injury in general (odds ratio [OR] = 1.1 per year, P = 0.05). For hamstring strains, the significant risk factors were age (OR = 1.4 [1 year], P < 0.001) and previous hamstring strains (OR = 11.6, P <0.001). For groin strains, the predictor risk factors were previous groin strains (OR = 7.3, P = 0.001) and decreased range of motion in hip abduction (OR = 0.9 [1 degrees ], P = 0.05). Previous injury was also identified as a risk factor for knee (OR = 4.6) and ankle sprains (OR = 5.3). CONCLUSIONS: Age and previous injury were identified as the main risk factors for injury among elite football players from Iceland.